Pilkada Serentak melalui DPRD: Sebuah Gagasan Mewujudkan Pilkada Demokratis Perspektif Pancasila dan UUD 1945 - Aziz, Mokhamad Abdul (Jurnal Politik Indonesia: Indonesian Political Science Review, 2016)
Unison in the succeeding organized the elections after December 9, 2015 as part of efforts to strengthen electoral democracy, Indonesia faced with the challenges of building a democratic substance. One that deserves to be evaluated is a system of direct election by the people. Although it has been conducted simultaneously, direct election is still too extravagant, yet produces the ideal leader, even a lot of them were involved in corruption cases, and most important their actions are not in line with the Indonesian democracy typical. Pancasila mandates that Indonesia's democracy is a democracy that is led by the inner wisdom of deliberations-representation. This is called modern democracy. Through Parliament elections simultaneously is the solution to realize the Indonesian democratic elections typical.